Late Adapters? How Social Workers Acquire Knowledge and Skills About Technology Tools. Issue 4 (1st October 2016) - Goldkind, Lauri; Wolf, Lea; Jones, Jamie
ABSTRACT: Little is understood about the scope of information and communication technology (ICT) use in practice for agency-based social work professionals, and still less is known about how such practitioners acquire and avail themselves of opportunities to learn about ICT tools. This study asked a sample of social work field supervisors ( n = 371) to describe their personal and professional ICT use, to rank the technological sophistication of their agency, to describe the barriers and facilitators to ICT use in their organizations and to operationalize environmental opportunities for acquiring new skills and knowledge. The authors examine factors that may influence technology use: asking if organizational culture is related to uptake in the professional context, and if self-reported individual resistance to innovation and change can explain voluntary adoption of ICT tools. The results offer a portrait of how agency-based social workers are using technology in personal and professional life, describe how these supervisors learn about developing technologies for practice, and highlight the gaps in technology infrastructures among agencies, pointing to directions for further exploration.